Identification of Environment Chase in Surround of Sermo Reservoir; and the Inﬂuence Possibility for Function and at the Age of Reservoi - Sudarmadji Sudarmadji (Forum Geografi, 2002)
Sermo reservoir is the only one belongs to Yogyakarta Special Province; it is relatively a new reservoir with the area of 1.9 kilometer square and its capacity of 25 million cubic meter: It started to operate since 1996 as flood control, irigation, water supply, tourism and ﬁshery purposes. As a reservoir it could be considered to be a manmade lake, as its condition nearly similar to a lake. Since it operated (even during construction period) there were some significant environmental changes within the reservoir and in the area around the reservoir due to the human activities. These changes could threat the sustainability of the reservoir itselfThis research aims to identiﬂr the human activities living around the reservoir and visitors coming to the area, and to evaluate the potensial of the activities to produce wastes which is discharging in into the reservoir; which may threat the sustainability of the reservoir: The observatorium in the ﬁeld has been conducted in the area of the reservoir and its sorrounding. I t was ﬁrund ﬁom the observation that activities o f ﬁshery using net (karamba), tourism altogether with its facilities, land use around the reservoir for agriculture purposes, mining of class C ore, have given a lot of contribution to wastes (liquid and solids) and sediments into the reservoir: Those activities may cause water quality of the reservoir lo decrease as well as reducing the reservoir depth. Those situation was observed in the northern and north western parts of the reservoir Water quality degradation of the reservoir may threat reservoir as source of domestic water supply, while the sedimentation may reduce the life time of the reservoir The fishery and tourism activities was estimated as a main cause of water quality degradation, beside agricultural and domestic wastes originated from sattlement area around the reservoir: Sediments coming into the reservoir are derived ﬁom transported and movement of materials from land slide occuring around the reservoir; due to distruction of land in constructing the relatively new ring-road close to the shore line of the reservoir: Of course, the sediment is also coming from rivers enteringdie reservoir. Sermo reservoir is a relatively young reservoir; the early observation of environmental changes of the reservoir could hopely be used as indicator to study ecological changes of the area within and around of the reservoir; and could be used as a comparison to other reservoirs, as well as basic environmental management of the reservoir and its surrounding.